2014
DOI: 10.1021/ja501923g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Reduction of CO2 to CO with High Current Density Using in Situ or ex Situ Prepared Bi-Based Materials

Abstract: The development of inexpensive electrocatalysts that can promote the reduction of CO2 to CO with high selectivity, efficiency, and large current densities is an important step on the path to renewable production of liquid carbon-based fuels. While precious metals such as gold and silver have historically been the most active cathode materials for CO2 reduction, the price of these materials precludes their use on the scale required for fuel production. Bismuth, by comparison, is an affordable and environmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
265
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(282 citation statements)
references
References 67 publications
15
265
1
1
Order By: Relevance
“…Occasionally, formate is identified as the main reduction product on Pd as probably mediated by the surface PdH x 82. There are also a handful of reports about Zn‐, In‐, or Bi‐based materials, mostly prepared from electrodeposition, for selectively reducing CO 2 to CO 83, 84, 85, 86, 87, 88, 89. Even though Co is commonly regarded as HER‐active, partially oxidized Co ultrathin layers surprisingly reduce CO 2 to formate at a very high Faradaic efficiency 90, 91.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…Occasionally, formate is identified as the main reduction product on Pd as probably mediated by the surface PdH x 82. There are also a handful of reports about Zn‐, In‐, or Bi‐based materials, mostly prepared from electrodeposition, for selectively reducing CO 2 to CO 83, 84, 85, 86, 87, 88, 89. Even though Co is commonly regarded as HER‐active, partially oxidized Co ultrathin layers surprisingly reduce CO 2 to formate at a very high Faradaic efficiency 90, 91.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…A single-step electrochemical process that can directly convert CO 2 to methane under conditions of ambient pressure and temperature may represent an attractive alternative. Of the metals explored as catalysts for electrochemical CO 2 reduction,(8) the most active and selective identified to date are gold, silver, and bismuth, (9)(10)(11)(12)(13)(14) which produce CO as their terminal product. Copper is attractive in comparison, as it produces more reduced hydrocarbon products.…”
mentioning
confidence: 99%
“…18 Rosenthal and co-workers have reported a generalized strategy for the electrodeposition of inexpensive electrocatalytic films from triflate salts of Bi 3+ , Sb 3+ , Sn 2+ , and Pb 2+ in organic media. [19][20][21] When the Bi-based electrodes are used for electrochemical CO 2 reduction in acetonitrile with a low overpotential of 250 mV, the 4 electrocatalysts are highly selective towards CO only when an appropriate ionic liquid is present in the system (1-ethyl-3-methylimidazolium hexafluorophosphate [EMIM]PF 6 , or 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM]PF 6 , with an average 81% CO FE with [25][26][27][28][29][30] mA cm −2 ). [19][20][21] These seminal studies have thus clearly indicated that non-noble catalysts have the capability to compete with noble metals for CO 2 reduction.…”
mentioning
confidence: 99%